Degree of compliance with the phototherapy guide in the neonate with jaundice in nurses of the Pampas - Huancavelica Hospital neonatology service 2019 - Otarola Torres, Gabriela Ruth (2020)
Objective:To identife the degree of compliance with the phototherapy guide in the neonate with jaundice in nurses of the Pampas - Huancavelica Hospital neonatology service 2019. Material and methods: The study variable was the degree of compliance with the phototherapy guide in the neonate with jaundice, with its five dimensions; thermoregulation, hygiene and comfort, food, safety and attachment.The methodology used was descriptive, using the non-experimental design descriptive type simple and cross-sectional. It was considered as a study area;15 nurses from the Pampas Hospital neonatology service, the sampling was non- probabilistic of an intentional type.The method used was scientific and descriptive, the instrument was an observation guide. Results: 74% nurses observed, if they comply with the phototherapy guide in the newborn with jaundice of the neonatology service. Conclusions: The degree of compliance with the phototherapy guide in the neonate with jaundice in nurses of the Pampas - Huancavelica Hospital neonatology service 2019 was identified. 74% of nurses do comply with the phototherapy guide in the neonate with jaundice.